Evaluation of damage caused by a cowpea weevil, Collosobruchus maculatus, in samples of cowpeas, Vigna sinensis, collected Fortaleza, Ceará, Brazil - Bastos, José Alberto Magalhães (Pesquisa Agropecuaria Brasileira, 2014)
Damage caused by Callosobruchus maculatus Fabricius (Coleoptera: Bruchidae) was calculated in 241 samples of cowpeas, Vigna sinensis Endl., collected in the open markets in Fortaleza, Ceará, Brazil. When these cowpea samples were purchased 27.80% had over 5% of the beans damaged. After 56 days of storage 68.46% of the samples had damage above the 5% level. Eight different merchants were asked to estimate the price of 15 samples and a mean price was calculated. The samples with 5% damage received a price reduction of 55.52%. Samples with 100% damage received a price reduction of only 81.27%.